Penilaian Kesesuaian Persediaan Bahan Habis Pakai Dalam Lingkup Standar Akuntansi Pemerintahan - Hendra Gunawan; Nur Andini (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2015)
The research aims to determine the valuation of inventory at the Hang Nadim Airport Batam. The data is processed using a qualitative approach and analyzed descriptively. Techniques of data collection using interviews, observation and documentation. The research concludes that there is conformity between the inventory valuation method Hang Nadim Airport Batam with Government Accounting Standards (SAP).